Russian world picture by means of the English language: time demand or “cultural caprice”? (Yuzefovich N.G. Interlinguacultural world picture in English of the second cultural orientation (on the material of description of Russian reality): monography. Kh (Proceedings of Southern Federal University. Philology, 2015)
Nikolaev S.G.Keywords: globalism, bilingualism, communicative space, communication, the English language.As an object of the work, the author of this article uses the monograph «Interlinguistic and cultural picture of the world in English of the secondary cultural orientation (based on the description of the Russian reality)» by Yuzefovich N. G. The author fully agrees with the opinion of Yuzefovich and he reinforces his view, using materials taken from the book, that in the conditions of the globalization the English language, which used to be taught at school has become outdated. In terms of modern communications, the term "bilingualism" is the key one. The author briefly describes each chapter of this monograph, emphasizes the information that is the most useful, in his view, and expresses his wish to add those aspects which Yuzefovich N. G. failed to  cover.